Exploration of synthetic multifunctional amides as new therapeutic agents for Alzheimer's disease through enzyme inhibition, chemoinformatic properties, molecular docking and dynamic simulation insights. (7th December 2018) - Hassan, Mubashir; Abbasi, Muhammad Athar; Aziz-ur-Rehman,; Siddiqui, Sabahat Zahra; Hussain, Ghulam; Shah, Syed Adnan Ali; Shahid, Muhammad; Seo, Sung-Yum
Highlights: Designing of multifunctional amides derivatives as acetyl and butyrylcholinesterase inhibitors. Chemoinformatic, molecular docking and simulation analysis was against most potent inhibitor7e. In vitro and in silico results showed the significance of7e and could be used as a template for novel drugs against Alzheimer's disease. Abstract: A new series of multifunctional amides has been synthesized having moderate enzyme inhibitory potentials and mild cytotoxicity. 2-Furyl(1-piperazinyl)methanone (1 ) was coupled with 3, 5-dichloro-2-hydroxybenzenesulfonyl chloride (2 ) to form 4-[(3, 5-dichloro-2-hydroxyphenyl)sulfonyl]-1-piperazinyl(2-furyl)methanone (3 ). Different elecrophiles were synthesized by the reaction of various un/substituted anilines (4a-o ) with 2-bromoacetylbromide (5 ), 2‑bromo‑ N -(un/substituted-phenyl)acetamides (6a-o ). Further, equimolar ratios of3 and6a-o were allowed to react in the presence of K2 CO3 in acetonitrile to form desired multifunctional amides (7a-o ). The structural confirmation of all the synthesized compounds was carried out by their EI-MS, IR, 1 H NMR and 13 C NMR spectral data. Enzyme inhibition activity was performed against acetyl and butyrylcholinestrase enzymes, whereby7e showed very good activity having IC50 value of 5.54 ± 0.03 and 9.15 ± 0.01 μ M, respectively, relative to eserine, a reference standard. Hemolytic activity of the molecules was checked to asertain their cytotoxicity towards red blood cell membrance and it was observed that most of the compounds were not toxic up to certain range. Moreover, chemoinformatic protepties and docking simulation results also showed the significance of7e as compared to other compounds. Based on in vitro and in silico analysis7e could be used as a template for the development of new drugs against Alzheimer's disease.